Preoperative endobronchial sanitation as preparation for thoracic interventions - Kritsak, Vasiliy; Ponomarova, Kateryna; Minukhin, Dmitriy (Scientific Route OÜ, 2020)
The aim – to study the effectiveness of endoscopic photodynamic therapy as a preoperative preparation of the tracheobronchial tree in patients with lung cancer. Materials and methods. The study included 181 patients with II–III stage of lung’s cancer. Diagnose of lung’s cancer was confirmed with a morphologically and concomitant endobronchitis. During the preoperative preparation, we used a technique developed by us introducing into the tracheobronchial tree an aqueous solution of brilliant green at concentration of 0.04 %, followed by irradiation of this solution with laser radiation with the wavelength of 0.63 μm (AFL-2 helium-neon laser) in an independent form and in combination with traditional anti-inflammatory therapy. Endoscopic endobronchial sanitation therapy was carried out by low-intensity radiation of the red part of the spectrum (λ=0.63–0.66 μm) in a pulsed mode, with a power of 12 mW. Results. After 3–5 days of the start preoperative preparation and 1–2 sessions of endoscopic bronchosanation, the general state of patients was improved, the amount of sputum decreased and was changing from mucopurulent to mucous. To completely stop the clinical phenomena of endobronchitis, it was necessary to conduct 5–6 sessions of endoscopic photodynamic therapy according to our methodology, with the introduction of our method. In patients without pronounced clinical symptoms of concomitant chronic bronchitis, it was enough to complete only 3 sessions of bronchosanation. Conclusion. Endoscopic photodynamic bronchosanation in the preoperative period in patients for correcting accompanying endobronchitis can significantly reduce or completely stop the clinical manifestations of endobronchitis in the shortest time and leads to a significant decrease in the number of endobronchial complications in surgical and combined treatment of lung cancer.
Keywords: preoperative preparation; endoscopic photodynamic therapy; complications